Aziatex Global Sdn Bhd / Muhammad Iqbal Azmi - Azmi, Muhammad Iqbal (Faculty of Business and Management, 2023)
The most memorable practical training within 6 months at Frame Sifu Trading Sdn Bhd, which located in Cheras Kuala Lumpur. This report discusses about the things that I did in the middle of practical training from 1st March 2023 until 15 August 2023. In this report, I attached some tasks that did for Account and Finance Department in the organization. So, in this report, I started with the introduction of the company that are consist of the background of the organization, the organizational structure and some introduction of the organization. Here also I mentioned about the products of the company and how the company manage their financial and database. Not to forget to mention the experience that I got during my practical training in this organization and about my new knowledge here. In the middle of the report, I attached the SWOT analysis which is strength, weaknesses, opportunities and treats about this organization. Last but not least, I also give some recommendation or ideas to the organization for their future use.